Support mechanisms provided by FLOSS foundations and other entities - Juho Lindman; Imed Hammouda (Journal of Internet Services and Applications, 2018)
Abstract Foundations function as a vital institutional support infrastructure for many of the most successful open-source projects, but the different roles played by these support entities are understudied in Free/Libre and Open Source Software (FLOSS) research. Drawing on Open Hub (formerly known as Ohloh) data, this paper empirically investigates how these entities support projects and interact with other projects. This study was conducted using the Theoretical Saturation Grounded Theory approach given the large volume of data on hand. The findings are synthesized as a taxonomy of support entities, a categorization of support mechanisms and a set of dynamics of the interactions between different FLOSS support entities.